Estimates of the economic cost caused by five major reproductive problems in dairy animals in Assam and Bihar, India - Deka, Ram Pratim; Magnusson, Ulf; Grace, Delia; Randolph, Thomas F.; Shome, R.; Lindahl, Johanna F. (MDPI, 2021)
Reproductive problems in dairy animals reduce fertility, prevent conception, create problems in the delivery of healthy calves, lead to postpartum complications, increase inter-calving periods, reduce milk yield, and lower overall lifetime productivity. This study aimed at understanding the incidence of reproductive problems and the cost caused by these. The study covered 954 dairy animals in Bihar and 1348 dairy animals in Assam that were selected using a multi-stage random sampling method. The costs were calculated as the sum of income losses and expenditures incurred. The major cost incurred resulted from extended calving intervals (46.1% of the total cost), followed by loss through salvage selling (38.1%), expenditure for treatment of repeat breeders (5.9%), loss of milk production (5.3%) and expenditure for extra inseminations (2.0%). About one fifth of the selected reproductive problems were left untreated. The estimated cost of reproductive problems was Indian Rupees (INR) 2424.9 (USD 36.1) per dairy animal per year (of the total dairy animal population) which represented approximately 4.1% of the mean value loss of dairy animals (INR 58,966/USD 877) per year. Reproductive problems were significantly (p < 0.001) higher among improved (exotic breed or cross-bred) dairy animals than indigenous (native breed or nondescript indigenous) dairy animals. The study suggests that with the increase of improved dairy animal population, the loss may further increase. The study concludes that any economic estimation of reproduction problems based on aetiology without confirmatory diagnoses could be highly misleading because of the complex nature of the problems.